2022
DOI: 10.1016/j.eclinm.2021.101258
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of paralyzed arm function in patients with hemiplegia through contralateral seventh cervical nerve cross transfer: a multicenter study and real-world practice guidance

Abstract: Background A previous randomized controlled trial showed contralateral seventh cervical nerve (CC7) cross transfer to be safe and effective in restoring the arm function of spastic arm paralysis patients in a specified population. Guidance on indications, safety and expected long-term improvements of the surgery are needed for clinical practice.Methods This is a retrospective, multicenter, propensity score-matched cohort study. All patients registered between 2013 and 2019 with unilateral spastic arm paralysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Comparing with other models, such as pyramidotomy lesion, we believe that TBI can better simulate the pathological state after unilateral cortical lesion and contribute to research the remolding of contralesional hemisphere better ( 33 ). However, clinical studies have confirmed that CC7 surgery has good effects on patients with hemiplegia caused by various diseases ( 7 , 34 ), the CST changes in various disease models of different species need to be evaluated in future study.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with other models, such as pyramidotomy lesion, we believe that TBI can better simulate the pathological state after unilateral cortical lesion and contribute to research the remolding of contralesional hemisphere better ( 33 ). However, clinical studies have confirmed that CC7 surgery has good effects on patients with hemiplegia caused by various diseases ( 7 , 34 ), the CST changes in various disease models of different species need to be evaluated in future study.…”
Section: Discussionmentioning
confidence: 99%
“…Contralateral C7 nerve transfer has been applied to improve upper limb spastic paralysis after stroke and has achieved good outcomes in terms of releasing spasticity, enhancing muscle strength, and improving voluntary motion coordination [ 5 7 ]. The procedure involves sectioning of the C7 nerve at the intervertebral foramen on the paralyzed side, which results in neuropathic pain [ 6 , 7 ]. We hypothesized that nerve division so close to the spinal cord is the crucial factor.…”
Section: Discussionmentioning
confidence: 99%
“…A new surgical strategy, contralateral C7 nerve transfer, has been introduced to improve upper limb function in stroke patients with upper limb spastic paralysis. This technique involves transferring the C7 nerve from the contralateral (nonparalyzed) side to the paralyzed side and has achieved considerable improvements in functional outcomes [ 4 7 ]. During the operation, the contralateral C7 nerve is sectioned as distally from the spinal cord as possible but proximal to the point at which it combines with other nerves; the ipsilateral C7 nerve (paralyzed side) is sectioned at the intervertebral foramen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously proposed that contralateral C7 transfer from the nonparalyzed side to the paralyzed side (contralateral C7 to C7 cross nerve transfer [CC7]) can effectively improve upper limb function [10, 11]. In the clinical follow-up of this surgery, post-stroke patients with complicated chronic aphasia surprisingly showed improvement in self-reported language function, not only in terms of fluency but also in terms of increased naming ability.…”
Section: Introductionmentioning
confidence: 99%